Research-related knowledge, understanding and practice in public mental health: the voices of social workers and occupational therapists - Christine Migliorini; Megan Turville; Caitlin McDowell; JoAnne Bevilacqua; Carol Harvey (BMC, 2024)
Abstract Introduction Previous studies have explored facilitators and barriers to research conducted by allied health professionals in general medical settings. Since the mental health system is acknowledged to be significantly under-funded and more poorly functioning than general medical services, it is unclear whether the published facilitators and barriers also apply to mental health settings. This study sought to explore the research-related knowledge, understanding and practices of allied mental health clinicians based in a large public mental health service. Methods A mixed methods study recruited 59 occupational therapists and social workers working in a dedicated metropolitan public mental health service in Melbourne, Australia. Quantitative survey results are reported elsewhere. Semi-structured interviews were conducted with 16 survey responder volunteers. Thematic analysis was conducted on the qualitative survey and interview data. Results Four main themes were identified: research must connect with clinical practice; fragments of knowledge; research in practice; and research is not part of my professional identity. The third theme, research in practice, comprised four subthemes: no time for research in clinical roles, missing communication, lack of ownership, and what I need to do research. Conclusions This study found that research and research-related activities were not considered part of the mental health social workers and occupational therapists' professional identities. Dealing with this issue may be instrumental to the realization of these clinicians' professional peak-body associations' code of practice and to government mandated practice standards. We provided several strategies to encourage both clinicians and services to view research-related activities as an everyday part of clinical roles. This is especially important if we think of allied health evidence-based practice requiring a reasonable level of research-related skills and/or competencies to appraise, practice, evaluate and adapt their evidence-based practice.